Pay agreement for Civic Restaurant and School Meals Staff, 1948 (pg. 1) (United Kingdom, 1948)
1948 1945-1960 "Pay agreement for Civic Restaurant and School Meals Staff, 1948 (pg. 1)" [HFR0054a], 1948 This National Union of Public Employees leaflet includes details of the first national agreement for women employed in local government school meals and Civic Restaurants. British Restaurants, established as local communal feeding centres in 1941, were renamed Civic Restaurants in 1946.